Trinity in unity in Christian-Muslim relations : the work of the Pontifical Council for Interreligious Dialogue - Jukko, Risto (History of Christian-Muslim relations, 2007)
Christian-Muslim relations are one of the major issues in contemporary theology of religions. This book deals with the theological foundations that have been laid for these relations in the official documents (1966-2005) of the Secretariat for Non-Christians/the Pontifical Council for Interreligious Dialogue.